Using multiple measures of language dominance and proficiency in Farsi-English bilingual children - Komeili, Mariam; Tavakoli, Parvaneh; Marinis, Theodoros (Frontiers in Communication, 2023)
This paper aims to identify effective means of measuring dominance and proficiency in bilingual children. 37 Farsi-English Heritage language speaking children from 6;1 to 11;6 were assessed on their vocabulary, morphosyntax, and narrative microstructure skills in both languages to address whether there is a difference between their proficiency in Farsi as a heritage and English as a majority language, how the scores on the vocabulary, morphosyntax, and narrative microstructure tasks relate to one another, and based on the results of each task in both languages if any of the children are at risk for a Developmental Language Disorder? Vocabulary was assessed using the LITMUS-CLT, morphosyntax using the LITMUS-SR tasks, and Narrative microstructure using the LITMUS-MAIN. Individual language proficiency was identified via an in-depth profile analysis for each participant which looked at their performance on all experimental tasks in both languages. The data demonstrated that on the vocabulary and narrative tasks the participants were more dominant in English than in Farsi, while on the SR task there were no significant differences between the two languages. Correlation analyses showed that vocabulary scores were strongly correlated to the SR scores and the microstructure scores. The English and Farsi SR scores also correlated moderately with the microstructure scores within each language. Profile analysis showed that no child within the study scored less than 1.5 or 2 standard deviations below the mean on more than two tasks in both languages. However, interesting patterns emerged indicating that some participants had a greater proficiency in one language versus the other language. The results from this study showed that measuring language within a single domain (e.g., morphosyntax) is not enough to identify a bilingual child’s language dominance and/or proficiency. Instead, an in-depth profile analysis and language assessments across various language domains need to be done in order to appropriately measure language dominance and proficiency. Consequently, this study supports the importance of measuring language across multiple domains in studies of bilingual children. The clinical significance of appropriately identifying language dominance and proficiency was also shown, as such information would allow clinicians to make more appropriate clinical decisions.